SISTEM INFORMASI PENJUALAN E-LIQUID NERD BOOKSHOP BERBASIS WEBSITE - - UBSI, Dwi Kuncoro (IJNS - Indonesian Journal on Networking and Security, 2020)
ABSTRACT - Nerd Bookshop is a shop engaged in the sale of used books, toys, vapor devices / e-cigarettes and E-Liquid. The manager of the Nerd Bookshop wants to market their products through online sales. This needs to be done because in the sales process the Nerd Bookshop still uses a manual process so that in carrying out its work activities it becomes less effective and efficient. The purpose of this research is to make it easier for customers to buy this product. In order to make it easier for customers to get information about available product prices and make it easier for the ordering process, as well as make it easier for the admin of the Nerd Bookshop company to manage data. Both product order data and member data. The method used in this research is the observation method, interview method, literature study, UML design methodology and waterfall system development method. As well as designing and building a website-based sales information system for the E-Liquid Nerd Bookshop that uses the PHP programming language and MySQL database. This research is expected to help companies manage sales administration activities, offer and sell E-liquid online to customers, while customers can order and buy books and can obtain information about E-liquid online via the internet, which can be done anytime and anywhere. just as a member. Keywords: Nerd Bookshop, Website, online ABSTRAK - Nerd Bookshop merupakan toko yang bergerak dibidang penjualan buku bekas, mainan, device vapor/rokok elektrik dan E-Liquid. Pengelola dari Nerd Bookshop ingin memasarkan produknya melalui penjualan secara online. Hal tersebut perlu dilakukan karena dalam proses penjualan pada Nerd Bookshop masih menggunakan proses manual sehingga dalam melakukan kegiatan kerjanya menjadi kurang efektif dan efisien. Adapun tujuan dari penelitian ini adalah untuk memudahan pelanggan untuk membeli produk ini memang sangat diharapkan. Agar memberikan kemudahan kepada pelanggan untuk mendapatkan informasi mengenai harga produk yang tersedia dan mempermudah dalam proses pemesanan, serta mempermudah admin perusahaan Nerd Bookshop dalam melakukan pengelolaan data. Baik data pemesanan produk maupun data member. Metode yang digunakan dalam penelitian ini adalah metode observasi, metode wawancara, studi pustaka, metodologi perancangan UML dan metode pengembangan sistem waterfall. Serta merancang dan membangun suatu sistem informasi penjualan E-Liquid Nerd Bookshop berbasis website yang menggunakan bahasa pemrograman PHP dan database MySQL. Penelitian ini diharapkan dapat membantu perusahaan dapat mengelola kegiatan administrasi penjualan, menawarkan dan menjual E-liquid secara online kepada pelanggan sedangkan untuk pelanggan dapat memesan dan membeli buku serta dapat memperoleh informasi tentang E-liquid secara online melalui media internet yang dapat dilakukan kapan saja dan dimana saja sebagai member. Kata kunci :Nerd Bookshop, Website, online